Interim Regimes and Businesspeople in Türkiye - Haluk Alkan (Yakın Dönem Türkiye Araştırmaları)
The relationship between military regimes, businesspeople, and economic policies has been analyzed from various perspectives in the literature. These studies have primarily examined the relationship between coups and economic growth and stability over the long and medium terms. Türkiye stands out from many other countries due to the relatively short duration of its coup periods. Nevertheless, interim regimes have left lasting effects on the economic policies and key actors representing businesspeople in Türkiye. This article seeks to identify the effects of interim regime periods on the representational structure and behavioral tendencies of businesspeople in Türkiye. To achieve this, the article first reviews the relevant literature and establishes the parameters of the analysis. It then analyzes the relationships between interim regimes and businesspeople in Türkiye during the periods of 1961-1965, 1971-1973, and 1980-1983. The study then delves into the long-term effects of policies, legal regulations, and new institutions developed during the military regime periods on business organizations at the sectoral level. The concluding section of the paper discusses the findings.